2021
DOI: 10.1136/bmj.n2182
|View full text |Cite
|
Sign up to set email alerts
|

Use of menopausal hormone therapy and risk of dementia: nested case-control studies using QResearch and CPRD databases

Abstract: Objective To assess the risks of developing dementia associated with different types and durations of menopausal hormone therapy. Design Two nested case-control studies. Setting UK general practices contributing to QResearch or the Clinical Practice Research Datalink (CPRD), using all links to hospital, mortality, and social deprivation data. Participants 118 501… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 20 publications
4
50
0
1
Order By: Relevance
“…Our study findings on HRT do not support associations between HRT and dementia risk, nor the aforementioned “timing hypothesis” for HRT initiation in relation to menopause for dementia risk. Consistently, a recent nested case–control study using a UK general practice cohort also found no evidence of an increased risk of dementia associated with menopausal hormone therapy; no evidence of different time of hormone therapy initiation may pose different risk of dementia [ 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…Our study findings on HRT do not support associations between HRT and dementia risk, nor the aforementioned “timing hypothesis” for HRT initiation in relation to menopause for dementia risk. Consistently, a recent nested case–control study using a UK general practice cohort also found no evidence of an increased risk of dementia associated with menopausal hormone therapy; no evidence of different time of hormone therapy initiation may pose different risk of dementia [ 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…Epidemiological evidence has been inconsistent with regard to risks of developing dementia. A study published in 2021 using a large data sample found that MHT use does not appear to increase the risk of developing dementia overall, but slightly increases the risk of developing Alzheimer's disease among long-term users of estrogenprogestogen therapies [38].…”
Section: Benefits and Risks Of Mhtmentioning
confidence: 99%
“…The characterization and suppression of the most relevant risk factors for AD onset and evolution have also been important research directions, simultaneously with the extensive study of potential protective factors. Among the most studied protective factors with strong evidence for reducing the risk of AD we mention cognitive reserves [ 21 ], exercise [ 22 ], and administration of hormone therapy during the peri- and postmenopausal period [ 23 ]. Moreover, also other factors such as Mediterranean diet [ 24 ], coffee intake [ 25 ], and use of non-steroidal anti-inflammatory drugs (NSAID) [ 26 ] showed weak evidence and often contradictory results related to their influence on AD onset and evolution.…”
Section: Introductionmentioning
confidence: 99%